Carcass characteristics of sexed broilers under two rearing systems in three housing zones in environmentally controlled broiler house during winter - Bilal, K.; Mehmood, S.; Akram, M.; Ahmad , S.; Hussain, J.; S. Jatoi, A.; M. Ishaq, H.; S. Shaheen, M. (Scientific Journal of Zoology, 2013)
The aim of study was to compare carcass characteristics of broiler housed under two different rearing systems (cage and floor) in three housing zones. For this purpose, 240 day old commercial broilers (Hubbard Classic) were purchased and half of them were reared in cages and other half on floor. Under each system, the birds were further divided in three zones of house (near vent, middle and near variable speed fans). There were four replicates containing 10 birds each. The data were analyzed through Analysis of Variance (ANOVA) technique in Completely Randomized Design (CRD) under factorial arrangements. Means were compared using Duncan’s Multiple Range Test (DMR) with the help of SAS 9.1. Pre-slaughter and post-slaughter weight of males rear on the floor exhibited significantly (P<0.05) higher body weight as compared with those rear in the cages. Similarly female attained significantly (P<0.05) higher body weight on floor as compared with those rear in the cages. Dressing percentage, breast weight, leg quarter yield, liver, heart and gizzard weight (filled & empty) in both sexes of broilers reared on floor was significantly (P<0.05) higher as compared to those reared in cages. Pre-slaughter body weight, post-slaughter body weight, Dressing percentage, higher breast weight, higher Leg quarter yields, liver, higher heart and gizzard weight (filled & empty) were found to be better near vents. It can be concluded from the present study that birds reared on floor perform better in area near the vent as compared to the cage.